2007
DOI: 10.1269/jrr.06103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin and Curcumin Copper Complex (1:1) on Radiation-induced Changes of Anti-oxidant Enzymes Levels in the Livers of Swiss Albino Mice

Abstract: The effect of mononuclear copper (II) complex of curcumin in 1:1 stoichiometry (hereafter referred to as complex) administered 30 min before gamma-irradiation (4.5 Gy) on alterations in antioxidant and Thiobarbituric acid reactive substances (TBARS) levels in livers was studied in comparison to curcumin at a dose of 50 mg/kg. The different antioxidants like GSH, GST, catalase, SOD, TBARS and total thiols were estimated in the liver homogenates excised at different time intervals (1, 2 and 4 h) post irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Similarly, in the present study OBX animals also showed a significant increase in lipid peroxidation and a marked decrease in the activity of reduced glutathione and catalase enzyme. Curcumin attenuated lipid peroxidation [47] and restored endogenous antioxidant profile [48] showing its powerful radical scavenging property [49]. In this study, OBX rats showed a significant increase in nitrite levels thereby implicating endogenous brain nitric oxide in the neurobiology of depression [50].…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, in the present study OBX animals also showed a significant increase in lipid peroxidation and a marked decrease in the activity of reduced glutathione and catalase enzyme. Curcumin attenuated lipid peroxidation [47] and restored endogenous antioxidant profile [48] showing its powerful radical scavenging property [49]. In this study, OBX rats showed a significant increase in nitrite levels thereby implicating endogenous brain nitric oxide in the neurobiology of depression [50].…”
Section: Discussionmentioning
confidence: 60%
“…Transition metal ions such as Cu(II), Zn(II), and Pd(II), have been established as one of the causes of Alzheimer's disease . A primary mechanism is their ability to catalyze polymerization of amyloid‐β and promote further misfolding of amyloid‐β into neurotoxic conformations found in brain cell plaques.…”
Section: Introductionmentioning
confidence: 99%
“…A primary mechanism is their ability to catalyze polymerization of amyloid‐β and promote further misfolding of amyloid‐β into neurotoxic conformations found in brain cell plaques. Curcumin appears to be a promising candidate as a chelating agent in scavenging these neurotoxic transition metal ions through a competitive chelate complexation mechanism . Moreover, curcumin prevents further misfolding of amyloid‐β into neurotoxic conformations that have been isolated in plaques of brain cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many recent studies show that the keto–enol moiety made unreactive by coordination with metal or other groups also show pharmacological properties of the order of curcumin or more . Curcumin coordinates with boron to form a 2:1 tetrahedral complex, rosocyanin (Fig.…”
Section: Introductionmentioning
confidence: 99%